USE OF ARTIFICIAL INTELLIGENCE IN THE DEVELOPMENT OF AUTOMATED INFORMATION SYSTEMS (American Journal of Technology and Applied Sciences, 2026)
This article examines the theoretical and practical aspects of applying artificial intelligence (AI) technologies in the creation of modern automated information systems (AIS). It analyzes the impact of AI algorithms on data processing speed, decision-making accuracy, and the adaptive characteristics of these systems.